Emerging treatments for postmenopausal osteoporosis – focus on denosumab - Piet Geusens (Dove Medical Press, 2009)
Piet GeusensDepartment of Internal Medicine, Subdivision of Rheumatology, Maastricht University Medical Center, Maastricht, The Netherlands and Biomedical Research Institute, University Hasselt, BelgiumAbstract: The pathway of the receptor activator of the nuclear factor κB ligand (RANKL), RANK and osteoprotegerin (OPG) plays a central role in coupling bone formation and resorption during normal bone turnover and in a wide spectrum of diseases characterized by disturbed bone remodeling, increased bone resorption and bone destruction (osteoporosis, Paget’s disease of bone, rheumatoid arthritis [RA], metastatic bone disease). Clinical trials indicate that denosumab, a RANKL-specific recombinant humanized monoclonal antibody, is effective in suppressing bone resorption, resulting in increase in bone mineral density (BMD) in postmenopausal women with low BMD, and has the potential to prevent progression of erosions in RA and of skeletal-related events in metastatic bone disease. The effects on fracture reduction in postmenopausal osteoporosis are awaited from the recently finished FREEDOM study. In clinical trials with denosumab, overall adverse events were similar to placebo or comparators, indicating a favorable safety profile in these diseases, which until now have been available up to 4 years, but data on long-term safety will be needed.Keywords: denosumab, postmenopausal osteoporosis, bone mineral density